E Maria vai com as outras: uma abordagem feminista sobre as mulheres na igreja - Lima, Soelma Costa da Fonseca (2011)
This research proposes to make an analytical study about gender relations that happen in the religious space of the church. The base portion of the study of feminist interpretation in dialogue with the actions of women leaders in churches today. The struggle of women in the Church does not aim to destroy traditions. The commitment of the feminist movement is an end to male domination and patriarchal structure. Thus, it is believed that there will be an achievement of rights but without taking the space of men. These writings also propose to raise discussions on the right of women to the priesthood, based on the biblical Mary Magdalene. It is a scary phenomenon to the androcentric culture, the ordination of women, as it has been expanding every day and with the authority until it is broken that paradigm sexist that a woman can not be the frontline in the Church. There will also be a dialogue redefines the concept of love and the search for the dignity of self, from Levinas.